MEMAKNAI KEMBALI AN-NISA’ AYAT 34: PENERAPAN KAIDAH “AL-DHARAR YUZAL” DAN RELEVANSINYA DENGAN PRINSIP PENDIDIKAN ORANG DEWASA - Matraji, Abdullah Ubaid (Institut PTIQ Jakarta, 2024)
This study aims to reinterpret surah an-Nisa verse 34 through the application of the ushul fiqh principle of al-dharar yuzal (harm must be eliminated) and its relevance to the concept of Adult Learning and Education (ALE). The primary focus of this study is to deconstruct the literal interpretation of the verse, which is often used to justify domestic violence. The research was conducted using a qualitative approach and a literature review method. The findings reveal that applying the principle of al-dharar yuzal in interpreting an-Nisa verse 34 can lead to a more humanistic, inclusive understanding that supports gender justice. This interpretation is also relevant in the context of ALE, which emphasizes reflective and dialogical learning in building harmonious, violence-free domestic relationships. This study offers practical and theoretical solutions to support societal transformation in understanding gender and domestic violence issues in alignment with Islamic fundamental principles